Secondary school teachers' approaches to teaching composition using digital technology. Issue 3 (7th December 2016) - Wise, Stuart
Abstract : The music industry in the 21 st century uses digital technology in a wide range of applications including in performance, in composition and in recording and publishing. In this article, I consider how the impact of digital technologies may be affecting pedagogical processes adopted by secondary music teachers, particularly in the area of composition. This paper examines qualitative data gathered from teachers in four schools participating in a larger research project. Data collected in this paper came from a number of semi-structured interviews. Findings indicate that although the majority of teachers involved in this research remain fundamentally conservative in their approaches to teaching composition, focusing on more procedural rather than creative activities, some music teachers do make radical changes to their pedagogy in contexts where this is important to their students' engagement and supported by their school.